Medidas de proteção de dados pessoais no planejamento e operação de smart grid utilizando computação em nuvem: estudo no contexto da Lei Geral de Proteção de Dados Pessoais (LGPD) do Brasil - Machado, Matheus Fogaca (2019)
The energy generation and consumption sector’s transition to the Smart Grid model has the potential to modernize the electric sector, increase the load availability, diversify the energy sources, and increase the use of electric vehicles, among other advantages. At the same time, the smart meters, imperative to the grid’s modernization, insert a new source of personal data that cause concern regarding the possibility of privacy invasion. This study aims to propose a set of measures for data protection in the Smart Grid planning and operation using cloud computing. A bibliographic survey was fulfilled through bibliometric survey and content analysis seeking to identify privacy threats and technical and organizational propositions of data protection in Smart Grids to subsidize the undertaking of a Data Protection Impact Assessment. The main results show that the measures are more effective when taken on the system planning and can orient its development to models that seek data minimization, mainly through use and collection limitation to the least amount necessary to perform each function, but also through cryptography and anonymization technics. The solely use of technical procedures on systems executing under the “collect first, process later” model may not be effective, reinforcing the importance of integrating data protection measures preemptively and thoroughly to the system’s components.